Economic activity and the terms of trade. Argentina, a case study - Buzzi, Sergio Martín (2015)
Fil: Buzzi, Sergio Martín. Universidad Nacional de Córdoba. Facultad de Ciencias Económicas. Instituto de Economía y Finanzas; Argentina.